Molecular diversity and functional dynamics in the central amygdala - Yeh, Li-Feng; Zuo, Shuzhen; Liu, Pin-Wu (Frontiers in Molecular Neuroscience, 2024)
The central amygdala (CeA) is crucial in integrating sensory and associative information to mediate adaptive responses to emotional stimuli. Recent advances in genetic techniques like optogenetics and chemogenetics have deepened our understanding of distinct neuronal populations within the CeA, particularly those involved in fear learning and memory consolidation. However, challenges remain due to overlapping genetic markers complicating neuron identification. Furthermore, a comprehensive understanding of molecularly defined cell types and their projection patterns, which are essential for elucidating functional roles, is still developing. Recent advancements in transcriptomics are starting to bridge these gaps, offering new insights into the functional dynamics of CeA neurons. In this review, we provide an overview of the expanding genetic markers for amygdala research, encompassing recent developments and current trends. We also discuss how novel transcriptomic approaches are redefining cell types in the CeA and setting the stage for comprehensive functional studies.